2016
DOI: 10.1002/mabi.201600337
|View full text |Cite
|
Sign up to set email alerts
|

Thin Poly(Di(Ethylene Glycol)Methyl Ether Methacrylate) Homopolymer Brushes Allow Controlled Adsorption and Desorption of PaTu 8988t Cells

Abstract: Poly(di(ethylene glycol)methyl ether methacrylate) (PDEGMA) brushes, which are known to suppress protein adsorption and prevent cell attachment, are reported here to possess interesting and tunable thermoresponsive behavior, if the brush thickness is reduced or the grafting density is altered. PDEGMA brushes with a dry ellipsometric thickness of 5 ± 1 nm can be switched from cell adherent behavior at 37 °C to cell nonadherent at 25 °C. This behavior coincides with the temperature-dependent irreversible adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 60 publications
13
38
0
Order By: Relevance
“…The LCST of PDGMA was reported to be 26 °C (for the bulk), , which increases to 32–34 °C for brushes. , In protein adhesion studies, we have previously determined an apparent surface transition temperature for end-grafted PDEGMA, which was reported to depend linearly on the PDEGMA thickness. ,, It increased from 35 °C for 5 nm thick PDEGMA layers to 48 °C at 23 nm. A very similar change in transition temperature could be achieved via a change of the PDEGMA grafting density, presumably via a transition from the mushroom to the brush regime.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LCST of PDGMA was reported to be 26 °C (for the bulk), , which increases to 32–34 °C for brushes. , In protein adhesion studies, we have previously determined an apparent surface transition temperature for end-grafted PDEGMA, which was reported to depend linearly on the PDEGMA thickness. ,, It increased from 35 °C for 5 nm thick PDEGMA layers to 48 °C at 23 nm. A very similar change in transition temperature could be achieved via a change of the PDEGMA grafting density, presumably via a transition from the mushroom to the brush regime.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dworak et al reported on poly­[tri­(ethylene glycol) ethyl ether methacrylate]-coated surfaces, polymerized on a solid substrate, which were employed for adhesion of fibroblasts and cell sheet formation as well as temperature-stimulated harvesting . More recently, PDEGMA homopolymer brushes were investigated and utilized for pancreatic tumor cell culture and cell detachment. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples are the properties of substrate-supported ultrathin polymer films, in which the values of the glass transition temperature ( T g ) and segmental mobilities were found to be altered. Likewise, this holds for transport properties, including polymer nanocapsule membrane permeability [1], enzyme-triggered bacterial sensors [25] and intelligent self-controlled drug delivery systems [4,610], as well as dynamics of polymers at interfaces [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the so‐called smart materials arose and drew much attention in the scientific community. Smart materials are stimuli‐responsive materials, which react to various stimuli, such as illumination, pH, temperature, chemical trigger, magnetic field, electric field, and deformation . For example, Xue et al proposed a thermoresponsive block copolymer coated mesh to separate water and oil.…”
mentioning
confidence: 99%